Corpus-based analysis of the collocational profiles of the terms denoting the mentally challenged - Markelova, Liana (Linguistik Online, 2017)
The present study aims to trace the evolution of public attitude towards the mentally challenged by means of the corpus-based analysis. The raw data comes from the two of the BYU corpora: Global Web-Based English (GloWbE) and Corpus of Historical American English (COHA). The former is comprised of 1.8 million web pages from 20 English-speaking countries (Davies/Fuchs 2015: 1) and provides an opportunity to research at a cross-cultural level, whereas the latter, containing 400 million words from more than 100,000 texts ranging from the 1810s to the 2000s (Davies 2012: 121), allows to carry on a diachronic research on the issue. To identify the difference in attitudes the collocational profiles of the terms denoting the mentally challenged were created. Having analysed them in terms of their semantic prosody one might conclude that there are certain semantic shifts that occurred due to the modern usage preferences and gradual change in public perception of everything strange, unusual and unique.